LIBERTATE ȘI NAȚIUNE: CONTEXT ȘI REPERE ALE MARII UNIRI (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Freedom and Nation: Context and Landmarks of The Great UnionThe Great Union from December 1st, 1918, is justly considered to be one of the historic moments in the history of the Romanian people, having important consequences both politically and socially. This event is an authentic historical process in which all provinces where Romanians lived were united in the same national state, Romania. Three main factors led to the articulation and realization of the idea of the unitary Romanian space: the ideological, political and military conjuncture at the European level, the existence of the intense national feeling among the Romanian population, as well as the determined political action of the elites in Wallachia, Moldova and the Austro-Hungary empire. The present paper is a modest attempt to review the main landmarks that have given way to the colossal national effort of 1918 which has succeeded in crystallizing the Romanians’ energies at a time of reference in their history.